Optimizing the Properties of Polyether Based Polyurethane Foam - Aramide, F. O.; Atanda, P. O.; Olorunniwo, E. O. (Scientific Research, 2013)
Effect of different chemicals and additives used in producing polyester foam was investigated. Reference samples were produced from polyol, toluene di isocyanate (TDI), amine stannous octoate distil water, and silicone oil using laboratory mix formulation based on 500 g polyether based polyol. Other samples were produced by consecutively varying the content of all the additives with the exception of polyol. Standard sample dimensions for density test, indentation test, compression set test, tensile strength and elongation tests were produced from the samples. The various tests were carried out on the samples using the ASTM-D3574 standards. It was observed that the degree of indentation affects the value of indentation hardness and increasing the percentage content of TDI results in acceptable compression set value for the polyester samples. It was concluded that Holding all other parameters constant, reducing the water content and increasing the TDI content will yield polyester foam of optimum properties.
Keywords: Hardness; Polyester Foam; Compression Set and Optimum Properties